2016
DOI: 10.3897/bdj.4.e8069
|View full text |Cite
|
Sign up to set email alerts
|

First record of Puerulus mesodontus Chan, Ma & Chu, 2013 (Crustacea, Decapoda, Achelata, Palinuridae) from south of Java, Indonesia

Abstract: BackgroundThree specimens of Puerulus mesodontus Chan, Ma & Chu, 2013 (Crustacea, Decapoda, Achelata, Palinuridae) were collected from Palabuhanratu Bay, southern Java, Indonesia. There is no previous record on the presence of the species in Indonesia. This finding represents the first record of this species in Java, Indonesia, and confirms that the species is present in the Indian Ocean. The morphological characters of the species are described.New informationThis paper contains a new distribution record of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 529 publications
(24 citation statements)
references
References 7 publications
1
21
0
2
Order By: Relevance
“…Many morphometric studies of decapod crustaceans have shown significant relationships among some morphometric characters to carapace or total length (e.g., Oh & Hartnoll 1999;Sampedro et al 1999;Conan et al 2001;Wardiatno & Tamaki 2001;Mashar & Wardiatno 2013a,b;Wardiatno & Mashar 2013;Muzammil et al 2015). Widely used allometric relationships have been used mostly to quantify the relative growth of body parts expressing secondary sexual characters in crustaceans (Hartnoll 1978(Hartnoll , 1982.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many morphometric studies of decapod crustaceans have shown significant relationships among some morphometric characters to carapace or total length (e.g., Oh & Hartnoll 1999;Sampedro et al 1999;Conan et al 2001;Wardiatno & Tamaki 2001;Mashar & Wardiatno 2013a,b;Wardiatno & Mashar 2013;Muzammil et al 2015). Widely used allometric relationships have been used mostly to quantify the relative growth of body parts expressing secondary sexual characters in crustaceans (Hartnoll 1978(Hartnoll , 1982.…”
Section: Discussionmentioning
confidence: 99%
“…Wardiatno and Tamaki (2001) revealed that variations in the size of the cornea and rostrum angle of Nihonotrypaea japonica and N. harmandi were effective characters to separate the two species. Wardiatno and Mashar (2013) speculated that variations in claw size between two mantis shrimp species (Harpiosquilla raphidea and Oratosquillina gravieri) may be a factor behind their competitive abilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Di Indonesia, ditemukan sebanyak tujuh jenis spiny lobster dari Famili Palinuridae yaitu Panulirus homarus (lobster pasir), P. ornatus (lobster mutiara), P. longipes (lobster batik), P. versicolor (lobster bambu), P. polyphagus (lobster pakistan/lumpur), P. penicillatus (lobster batu) (Phillips, 2006;Tewfik et al, 2009), dan Puerulus mesodontus (Wardiatno et al, 2016). Kalih (2012) …”
Section: Pendahuluanunclassified